Impaired Mitochondrial Transcription Factor A Expression Promotes Mitochondrial Damage to Drive Fibroblast Activation and Fibrosis in Systemic Sclerosis - Zhou, Xiang; Trinh, Minh Thuong; Tran Manh, Cuong; Gießl, Andreas; Bergmann, Christina; Györfi, Andrea-Hermina; Schett, Georg; Distler, Jörg (Arthritis and Rheumatology, 2022)
Objective Mitochondrial transcription factor A (TFAM) controls the transcription of core proteins required for mitochondrial homeostasis. This study was undertaken to investigate changes in TFAM expression in systemic sclerosis (SSc), to analyze mitochondrial function, and to evaluate the consequences for fibroblast activation. Methods TFAM expression was analyzed by immunofluorescence and Western blotting. The effects of TFAM knockout were investigated in cultured fibroblasts and in murine models of bleomycin-induced skin fibrosis, bleomycin-induced lung fibrosis, and skin fibrosis induced by overexpression of constitutively active transforming growth factor beta type I receptor (TGF beta R Iota). Results TFAM expression was down-regulated in fibroblasts in SSc skin and in cultured SSc fibroblasts. The down-regulation of TFAM was associated with decreased mitochondrial number and accumulation of damaged mitochondria with release of mitochondrial DNA (mtDNA), accumulation of deletions in mtDNA, metabolic alterations with impaired oxidative phosphorylation, and release of the mitokine GDF15. Normal fibroblasts subjected to long-term, but not acute, exposure to TGF beta mimicked SSc fibroblasts, with down-regulation of TFAM and accumulation of mitochondrial damage. Down-regulation of TFAM promoted fibroblast activation with up-regulation of fibrosis-relevant Gene Ontology terms in RNA-Seq, partially in a reactive oxygen species-dependent manner. Mice with fibroblast-specific knockout of Tfam were prone to fibrotic tissue remodeling, with fibrotic responses even to NaCl instillation and enhanced sensitivity to bleomycin injection and overexpression of constitutively active TGF beta RI. TFAM knockout fostered Smad3 signaling to promote fibroblast activation. Conclusion Alterations in the key mitochondrial transcription factor TFAM in response to prolonged activation of TGF beta and associated mitochondrial damage induce transcriptional programs that promote fibroblast-to-myofibroblast transition and drive tissue fibrosis.
CRIS-Team WoS Importer:2022-04-15